Salvation through slavery : Chiricahua Apaches and priests on the Spanish colonial frontier - Stockel, H. Henrietta, 1938- (University of New Mexico Press, 2008)
Stockel examines the brutal history of forced conversion and subjection of the Chiricahua Apaches by Spanish priests during the seventeenth and eighteenth centuries.